Factors influencing Agrobacterium-mediated genetic transformation efficiency in bread wheat (Triticum aestivum L.) - Thiyagarajan, Karthikeyan; Noguera, Luis Miguel; Pacheco, Mario; Govindan, Velu; Vikram, Prashant (Indian Society of Genetics and Plant Breeding, 2024)
Assessment of the efficiency of Agrobacterium tumefaciens mediated transformation in four bread wheat varieties was focused and upon optimization of experiments done to obtain tangible results. The four varieties, Fielder, Navojoa, Baj and Kachu/saul, were transformed with optimized protocols and randomly selected from a selection medium amalgamated with phosphinothricin (Glufosinate). Initially, the variety Fielder has proceeded with 36 different concentrations of synthetic auxins 2,4-D and picloram as 36 treatments. The treatment 30 (48 µg of 2,4-D and 64 µg of picloram) has shown higher efficiency and is comparable in terms of the three traits studied. Additionally, antioxidants and growth regulators were adjusted to obtain better results towards reasonable transformation frequency. Additional varieties were also tested and selected against the selectable marker PPT based on the optimization for the variety Fielder. Selected genotypes were subjected for gusA or Bar gene PCR amplification. The result revealed the frequency of transgenesis in the range of 60 to 70% with the varieties studied. However, the whole experiment needs further repetitions for confirmatory results. Transgenic genotypes of the Fielder variety showed moderate to strong GUS expression in leaves, anthers, seeds, seed coats, and roots compared to non-transgenic control plant tissues. PPT leaf painting assay showed the lack of necrosis on the painted area of leaves in transgenic genotypes compared to the non-transgenic ones.